Approximate solutions for solving nonlinear variable-order fractional Riccati differential equations - Doha, Eid H. H.; Abdelkawy, Mohamed A. A.; Amin, Ahmed Z.M. Z.M.; Baleanu, Dumitru (Nonlinear Analysis: Modelling and Control, 2019)
In this manuscript, we introduce a spectral technique for approximating the variable-order fractional Riccati equation (VO-FRDEs). Firstly, the solution and its space fractional derivatives is expanded as shifted Chebyshev polynomials series. Then we determine the expansion coefficients by reducing the VO-FRDEs and its conditions to a system of algebraic equations. We show the accuracy and applicability of our numerical approach through four numerical examples.